How do automation and offshorability influence unemployment duration and subsequent job quality? - Bernhard Schmidpeter; Rudolf Winter-Ebmer (Johannes Kepler University of Linz, Department of Economics, 2018)
We analyze the effect of automation and offshorability on unemployment duration and postunemployment outcomes such as wages and employment stability. Our rich administrative data allow us to evaluate the importance of providing unemployment training in this context. Employing a multivariate mixed proportional hazard model to deal with selectivity, we find that both the routine content in tasks as well as the probability of off-shoring negatively affects the re-employment possibilities. Labor market training is helping workers to ameliorate these negative effects and is remarkably on the spot. For workers who find re-employment, our results show that offshorability (but not automation) affects future job duration and wages positively. Our analysis reveals interesting differences by gender.
Keywords: 330; routinisation; offshoring; unemployment duration